Aluminum and silver removal using Lemna minor - Lizcano Toledo, Mayra (2023)
Water pollution by metals is a problem that jeopardizes the health of living organisms on the planet. This document presents the results of the removal capacity of the macrophyte Lena minor for aluminum and silver. The methodology used consisted of exposing the macrophyte, under in vitro conditions, to concentrations of 2 and 3 ppm of the selected metals. After one week, analysis was carried out using molecular absorption spectrophotometry, from which it was determined that lemma minor showed efficient removal of aluminum, while in the case of silver, only 10% removal was obtained. Considering the phytotoxicity presented, it is not recommended for use. Finally, a comparison was made with the removal of other macrophytes for these metals, and it was identified that this macrophyte is suitable for use in the subtraction of aluminum.